Digital analysis of distant and cancer-associated mammary adipocytes. (December 2020) - Isnaldi, Edoardo; Richard, François; De Schepper, Maxim; Vincent, Delphine; Leduc, Sophia; Maetens, Marion; Geukens, Tatjana; Floris, Giuseppe; Rouas, Ghizlane; Cardoso, Fatima; Sotiriou, Christos; Zoppoli, Gabriele; et al.
Abstract: Adipocytes and cancer-associated adipocytes (CAAs) are poorly investigated cells in the tumor microenvironment. Different image analysis software exist for identifying and measuring these cells using scanned hematoxylin and eosin (H&E)-stained slides. It is however unclear which one is the most appropriate for breast cancer (BC) samples. Here, we compared three software (AdipoCount, Adiposoft, and HALO®). HALO® outperformed the other methods with regard to adipocyte identification, (> 96% sensitivity and specificity). All software performed equally good with regard to area and diameter measurement (concordance correlation coefficients > 0.97 and > 0.96, respectively). We then analyzed a series of 10 BCE samples (n = 51 H&E slides) with HALO®. Distant adipocytes were defined >2 mm away from cancer cells or fibrotic region, whereas CAAs as the first three lines of adipocytes close to the invasive front. Intra-mammary heterogeneity was limited, implying that measuring a single region of ∼500 adipocytes provides a reliable estimation of the distribution of their size features. CAAs had smaller areas (median fold-change: 2.62) and diameters (median fold-change: 1.64) as compared to distant adipocytes in the same breast (both p = 0.002). The size of CAAs and distant adipocytes was associated with the body mass index (BMI) of the patient (area: rho = 0.89, p = 0.001; rho = 0.71, p = 0.027, diameter: rho = 0.87 p = 0.002; rho = 0.65 p = 0.049, respectively). To conclude, we demonstrate that quantifying adipocytes in BC sections is feasible by digital pathology using H&E sections, setting the basis for a standardized analysis of mammary adiposity in larger series of patients. Highlights: Mammary adiposity is under-investigated in the context of breast cancer. Digital pathology can measure adipocytes distant from the tumor as well as cancer-associated adipocytes (CAAs). CAAs are smaller than distant adipocytes, reflecting the delipidation process undergone by CAAs. The body mass index of the patient is associated with the size of distant adipocytes and CAAs.